DAMPAK OPEN DOOR POLICY YANG DITERAPKAN DENG XIAOPING TERKAIT PENINGKATAN SEKTOR INDUSTRI CINA PASCA RERORMASI 1978 - Gde Restu Adhi, Ida Bagus (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2012)
Purpose of this research is to understand relation between Open Door Policy that applied in China under leadership of Deng Xiaoping with improvement of industrial sector in China. Data collection is done by library research and internet. Writer found that open door policy which embedded in China’s economic reform in 1978 has given enormous advantage to Improvement of industrial sector in China. step by step foreign investment come to China which aspirated with transfer technology. Improvement of industrial sector in China indirectly give such a significant impact to China’s economic growth in general. With the result that now China has become one of the countries with massive economic growth which overcome other developing countries in the world and become 2nd largest reserve of foreign exchange after United States of America.